Pengembangan Materi Etnobotani Dalam Mendukung Konsep Dasar Pembelajaran IPA Di Perguruan Tinggi - Zulharman Zulharman; Mochamad Noeryoko (Postgraduate, University of Mataram, 2023)
The local knowledge of the Doridungga Donggo community in searching for medicinal and food ingredients is a form of wisdom because its use follows ecological rules. The use of these plants can be in the form of plants with medicinal properties that are used for treatment by communities around forest areas as traditional medicine. The research aims to investigate medicinal ingredients from conventional plants of the Doridungga Donggo community, which can be used to strengthen science learning concepts. Data sources and information on research data sources were determined using purposive sampling techniques. Data sources were selected based on primary data and secondary data. Preliminary data was obtained from the results of site surveys and supported by secondary data from various literature on ethnobotany. The research was conducted in Doridungga Village, Donggo District, Bima Regency, NTB. Data was analyzed based on characteristic values, theoretical plant benefits, and plant benefits based on community perception. The research results include Bidara, Guava, Golkar, Turmeric, Betel, Pule, Coriander, Kicibling, and Rida Fada. These plants are used as medicine for fever, stomach ache, diabetes, stomach ulcers, to remove body odor and bad breath, tuberculosis, wounds, tonsils, urinary syphilis, headaches, and lumbago. The research results can be input for university science learning curricula based on local wisdom